Kandungan fitokimia dan aktivitas antibakteri ekstrak etanol biji buah nyirih (Xylocarpus granatum ): Phytochemical and antibacterial activity of ethanol extract from cannonball mangrove (Xylocarpus granatum) fruit seeds - Khairina, Rita; Sari, Dewi Kartika; Fitrial, Yuspihana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Xylocarpus granatum (cannonball mangrove) is a mangrove species known as nyirih fruit in South Kalimantan. This study aims to determine the phytochemical content and antibacterial activity of the seeds from X. granatum fruit. The research stages included preparing cannonball mangrove fruit into powder, extracting the seed powder with ethanol, conducting phytochemical tests on the seed powder, preparing test bacteria, and testing the antibacterial properties of the ethanol extract from the cannonball mangrove seeds. The parameters tested were yield, proximate, phytochemical, and antibacterial tests against E. coli and S. aureus. The yield of cannonball mangrove fruit seeds was 21.17%, and the powder weight was 7.04%. Cannonball mangrove fruit seed powder contains 4.97% water content, 2.56% ash, 4.54% protein, 0.63% fat, and 2.5% crude fiber. Cannonball mangrove fruit seed powder contains saponins, alkaloids, flavonoids, tannins, triterpenoids, phenolics, steroids, and anthocyanins. The results of the antibacterial test showed that increasing the concentration of ethanol extract of cannonball mangrove fruit seed powder was inversely proportional to the total bacteria but directly proportional to the percent inhibition. Extracts of 20-90 µL showed total E. coli bacteria of log 9.32 CFU/g and log 1.18 CFU/g with percent inhibition of 5.93 and 88.05%. Extract concentrations of 1-15 µL against S. aureus bacteria showed total bacterial values of log 5.69 CFU/g and log 8.65 CFU/g with percent inhibition of 29.37 and 64.46. Antibacterial testing with the direct contact method showed the ability of ethanol extract of cannonball mangrove fruit seed powder to inhibit the growth of E. coli and S. aureus bacteria at low extract concentrations.